CORRELATION AND INTERACTION BETWEEN THE SOCIAL PHOBIA AND TEST ANXIETY - Rulić, Katarina B; Latas, Milan (Medicinski podmladak, 2017)
Introduction: A considerable number of students, who experience high rates of test anxiety, are faced with problems before or during test/exam situations.Anxious behaviour creates barriers to learning and taking exams, contributes to low test performances and makes students leave their studies. This leads to students’ negative self-evaluation and possible disruption of their lives.                                                                                 The Aim: The aim of the present research is to establish potential connections between a social phobia and test anxiety with polled students in order to make them susceptible to more appropriate treatment and enable them to lead normal lives. Preventive measures taken with younger generationes could inhibit  the development of anxiety at early stage and comorbid anxiety disorders as a consequence.                                                                                                                                                                                                         Material and Methods: The research involved 120 students of the first and fourth years of studies.To determine the level of the social phobia we used Social Phobia Inventory–SPIN, and The Test Anxiety Inventory–TAI to estimate the degree of test anxiety.                     Results: The results confirmed connections between a social phobia and test anxiety with a certain number of students in respect to their average mark during the studies as well as to their parents expectations’ and their loss of self-confidence. We did not establish the connection with students ’ economic position or with anxiety connection in terms of gender, because the female student population was much higher than the male population, so the results would not be valid.                                                                              Conclusion: The result we have obtained show that there is statistically significant evidence of connection betwen a social phobia and test anxiety with the polled students, the fact which can facilitate their treatment and prevention with younger generations.                                                                                                                                Key words: Social phobia, test anxiety, social anxiety disorder, fear of evaluation, inventories.